What will replace sociology? - Hartman, Jan (Journal of Public Governance, 2013)
The article offers an analysis of the theoretical and social condition of social sciences and their prospects. Long ago, social sciences managed to ritualize the ‘crisis discourse’ that has perpetuated itself since. Deriving benefits from repeatedly diagnosing its own crisis is an ethically dubious pursuit. The same observation applies to the incessant revisiting of the dialectics of involvement and non-involvement, in other words, description versus evaluation. The inevitability of axiological commitment of sociology often becomes an alibi for being satisfied with appearances only. Sociology is not innocent. It impacts social consciousness by supplying the middle class and elites with tools that help them strive for self-awareness, which results in the emergence of a ‘society of self-taught sociologists’. Sociology has changed society, imposed its own idiom on it, but it refuses to accept responsibility for the consequences of this fact. It is sceptical and infects society with its scepticism. If the sociological discourse was meant to be therapeutic, it has failed. The author of the article claims that sociology must enter its ‘post’ phase, that is, transform into something that will no longer be construed as sociology. In so doing, the author critically analyzes several assumptions (usually) adopted by social sciences, since the future of social sciences and the future of society are very closely intertwined.